Asbabun Nuzul Khass dan Haqiqi Perspektif Syah Waliyullah Ad-Dahlawi - Gilang Saputra (STAIN MAJENE, 2025)
This article explores the concept of asbābun nuzūl from the perspective of Shah Waliyullah al-Dihlawi, an 18th-century Islamic reformer. Traditionally, the study of asbābun nuzūl has often focused on partial and fragmented reports (khass), which may obscure the essential meaning of the Qur’anic verses. Al-Dihlawi introduces a distinction between asbābun nuzūl khass and asbābun nuzūl haqiqi. The former refers to classical reports that are often historically unreliable, while the latter emphasizes understanding the broader socio-cultural and moral context of Arabian society during the revelation. This approach allows for a more comprehensive and contextual interpretation of the Qur’an. Using a library research method, this study examines both classical and contemporary literature on asbābun nuzūl. The findings indicate that Al-Dihlawi’s thought significantly contributes to shifting the paradigm of asbābun nuzūl from a micro to a macro approach, paving the way for modern contextual interpretations of the Qur’an.